Otoplasty in Children with Prominent Ears: A Scoping Review - Handari, Eva Tami; Koento, Trimartani (PERHATI-KL, 2025)
Background: Prominent ears are one of the most common facial deformities in children. Although primarily a cosmetic issue, this condition can have significant social and psychological impacts on children, leading to the need for otoplasty at an early age. Otoplasty, a corrective surgical procedure, has undergone various innovations aimed at achieving satisfactory aesthetic outcomes, while minimizing complications. Purpose: To convey surgical techniques used in otoplasty for children with prominent ears. Case report: A 5-year-old patient presented with complaints of absent external auditory canals and prominent ears. The patient was diagnosed with bilateral auricular atresia, and prominent ears. The parents also reported speech delay in their child. Otoplasty was performed using the latest technique, with adjustments to the antihelical fold and reduction of conchal projection. Result: Following otoplasty using the newly introduced setback otoplasty technique described by Raunig, the patient demonstrated significant improvement in the aesthetic appearance of the ears with a more harmonious projection. Postoperative complications were minimal, with no signs of infection or residual deformity. The patient also continued postoperative speech therapy to address the speech delay. Conclusion: Advances in otoplasty with the New Concept Rauning technique had proven effective in correcting prominent ear deformities in children, yielding favorable aesthetic outcomes, with minimal complications. Early otoplasty can correct ear shape abnormalities and improve the child’s quality of life, both cosmetically and psychosocially.